(untitled) (Asian Journal of Medical and Biological Research, 2016)
Chia (Salvia hispanica L.) contains the highest level of omega- 3 fatty acid available in any cultivated plant source. The objective of this research was to find out the suitable planting time for chia in Bangladesh and to study the effect of planting time on its growth and yield. An experiment was carried out at the field laboratory of the Department of Crop Botany, Bangladesh Agricultural University (BAU), Mymensingh, during the period from November 2013 to July 2014 to study the growth, morpho-physiological yield contributing characters and yield of chia. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. The collected data were analyzed statistically and the means were adjudged by DMRT using the statistical computer package program, MSTAT_C. The tallest plant (136 cm), highest number of inflorescence plant1 (13.67), highest amount of total dry matter (305 g) and highest root length (7.767 cm) were recorded from November planting at harvest. However, leaf area plant1 (207.2 cm2) and LAI (1.891) had also significantly higher from November planting at 90 days after sowing (DAS) compared to other planting times. November planting further recorded the higher CGR (33.43 g m-2 day-1) at the stage between 7690 DAS and thereafter they decreased. Higher seed yield (1033 Kg ha1), husk yield (888 Kg ha1), seed yield plant-1 (4.773 g), husk yield plant-1 (2.840 g) were also recorded from November planting. In December planting the seed yield, husk yield, seed yield plant-1, husk yield plant-1 were 681 Kg ha1, 340 Kg ha1, 2.350g and 0.9467g, respectively. Lower seed yield (159 Kg ha1), husk yield (166 Kg ha1), seed yield plant-1 (0.6150 g) and husk yield plant-1 (0.5383 g) were recorded from January planting. Except total dry matter, other morpho-physiological characters, yield and yield contributing factors were less effective in January than other planting time. February and March planting did not produce any fertile spike resulting yield less vegetative growth. These results revealed that, November planting was found outstanding superiority for plant growth, yield and morpho-physiological characters of chia in Bangladesh. Asian J. Med. Biol. Res. December 2015, 1(3): 502-507